The Length of a Wide Highway: On the Archive, the (Electronic) Marketplace, and the End of a Collection - Wild, Jennifer (Cinémas)

(untitled) (Cinémas, 2014)
This essay is an image-driven reflection on the archive, the collection and collecting, and the act of acquisition. Using parts of her collection of cinema-related ephemera, the author draws on the writing of Apollinaire, Benjamin, Canudo, Derrida, and Dugas to animate questions about their ownership and their place and function in both the archive and the activities of writing and research. By also examining the dynamics of real and virtual marketplaces, the author in turn explores how questions concerning reproduction, purchasing and repetition inhabit the theoretical strata of today’s archive, as well as comprise the archival strata of the collection itself.